Behavior Nurse and Infection Prevention and Control - Puspitasari, Putri Widiana; Hutahaean, Serri (Sarana Ilmu Indonesia (salnesia), 2023)
Healthcare-associated infections (HAIs) are one of the health problems experienced by almost all countries, including Indonesia. Cross-infection is one of the infections that affect HAIs, nurses are the ones who work in hospitals and interact with patients for 24 hours. The purpose of this study was to determine the relationship between the role and behavior of nurses and the characteristics of subjects with infection prevention and control measures. This research was conducted in June 2023 at Dr. Sitanala Tangerang Hospital. This research method used quantitative with a cross-sectional approach. Sampling was a total sampling of 100 subjects. The research instrument was using a questionnaire in the form of a G-Form. The data were then analyzed by using the chi-square test. The results of the study obtained a p-value<0,05 (0,009) meaning that there was a relationship between nurse behavior and infection prevention and control. The recommendation from this study is the need for action from hospital management to improve the quality of nurses by providing training or support for infection prevention and control measures in order to maximize infection prevention and control measures.